Analisis Religiusitas Dan Kesadaran Halal Dalam Meningkatkan Literasi Sertifikasi Halal Pada Masyarakat Kecamatan Lenteng Kabupaten Sumenep - Eka Suci Istiarini; Lailatul Qadariyah; Sarkawi Sarkawi (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This research aims to analyze the level of religiosity and halal awareness of the people of Sumenep Regency in increasing halal certification literacy. Halal certification is an important aspect in product consumption for Muslims, however literacy regarding halal certification is still relatively lacking. The Madurese community, especially in Lenteng District, Sumenep Regency, is known to the public for their high level of religiosity and halal awareness, but it is not necessarily the case that with the high religiosity and halal awareness possessed by the people of Sumenep Regency, their halal certification literacy level is good. In reality, there are still many MSMEs that do not have halal certification for their products. For this reason, this research will discuss religiosity and halal awareness in increasing halal certification literacy in the community in Sumenep Regency. The research method used in this research is a descriptive qualitative research method, where the data search process is carried out through interview and documentation techniques. The data source was obtained directly through interviews with 10 respondents from the people of Lenteng District, Sumenep Regency. The results of this research show that the religiosity and awareness of the people of Lenteng District are quite good, but the people of the District in terms of halal certification literacy are at the Sufficient Literate level because most of them only know about halal certification through the halal logo but they still don't understand the process of making halal certification.